2017
DOI: 10.1097/ccm.0000000000002522
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Moderate Hyperchloremia on Clinical Outcomes in Intracerebral Hemorrhage Patients Treated With Continuous Infusion Hypertonic Saline: A Pilot Study

Abstract: We observed higher rates of in-hospital mortality in patients who developed moderate hyperchloremia during treatment with continuous IV infusion 3% hypertonic saline, with moderate hyperchloremia independently predicting in-hospital mortality. These results suggest that chloride values should be monitored closely during hypertonic saline treatment as moderate elevations may impact outcomes in intracerebral hemorrhage patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
32
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 31 publications
7
32
1
1
Order By: Relevance
“…Similar to these studies, we observed that both new-onset hyperchloremia or every 5 mmol/L increment in Δ[Cl − ] were associated with increased odds of poor outcome in critically ill stroke patients, although these two variables did not show independent significance in multivariate models. The possible explanation could be that the prevalence of hyperchloremia in our subjects (17.0% in the first 72 h) was much lower than that in other patient groups [65.3% ( 13 ) in patients with ICH and treated with hypertonic saline; 40.8% (( 10 )) and 31.7% ( 9 ) in patients with septic shock].…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Similar to these studies, we observed that both new-onset hyperchloremia or every 5 mmol/L increment in Δ[Cl − ] were associated with increased odds of poor outcome in critically ill stroke patients, although these two variables did not show independent significance in multivariate models. The possible explanation could be that the prevalence of hyperchloremia in our subjects (17.0% in the first 72 h) was much lower than that in other patient groups [65.3% ( 13 ) in patients with ICH and treated with hypertonic saline; 40.8% (( 10 )) and 31.7% ( 9 ) in patients with septic shock].…”
Section: Discussioncontrasting
confidence: 55%
“…Hyperchloremia has been reported to be associated with increased hospital mortality and negative outcome in critically ill patients ( 8 ), with severe sepsis and septic shock ( 9 , 10 ), as well as after surgery and trauma ( 11 , 12 ). In patients with ICH, a recent study demonstrated higher rates of in-hospital mortality in those who developed moderate hyperchloremia during treatment with continuous intravenous infusion of 3% hypertonic saline, with moderate hyperchloremia independently predicting in-hospital mortality ( 13 ). Another study in patients with subarachnoid hemorrhage found a strong association between hyperchloremia and acute kidney injury (AKI) as well as AKI and mortality ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to recent evidence in patients with other underlying neurological pathologies, hyperchloremia may have an impact on overall clinical outcomes in this patient population. 11 -13…”
Section: Discussionmentioning
confidence: 99%
“…11 A multicenter study of patients with intracerebral hemorrhage (ICH) identified moderate hyperchloremia (≥115 mmol/L) as an independent predictor of inhospital mortality. 12 Finally, a study evaluating a mixed cohort of patients with hemorrhagic and ischemic stroke found that hyperchloremia (>110 mmol/L) development within 72 hours of admission was also associated with increased mortality. 13 To date, no study has examined the effects of hyperchloremia solely in acute ischemic stroke (AIS), although it accounts for nearly 87% of strokes in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, we included patients with preoperative CKD and adjusted for CKD in the multivariable logistic analysis. In addition, several studies that reported an association between hyperchloremia and AKI in patients with major trauma [ 20 ], subarachnoid hemorrhage [ 8 ], severe sepsis or septic shock [ 7 ], or intracerebral hemorrhage [ 21 ] included patients who received large volumes of NaCl 0.9%. Our study differs from those previous investigations in that we included patients who were admitted to the ICU after undergoing any type of surgery.…”
Section: Discussionmentioning
confidence: 99%